The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1088/0067-0049/186/1/85
|View full text |Cite
|
Sign up to set email alerts
|

RADIATIVE L-SHELL TRANSITIONS IN Fe XIX AND Fe XX IONS

Abstract: We compute the wavelengths and oscillator strengths for the 3s, 3d → 2p, and 3p → 2s emission lines in Fe xix and Fe xx ions by using a configuration interaction Dirac-Fock and Dirac-Fock-Sturm method combined with second-order Brillouin-Wigner perturbation theory. We provide a complete list of computed wavelengths and oscillator strengths in both the velocity and length gauge for these transitions, many of which have never previously been reported. A comparison of our data with laboratory measurements and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The data sets of the n ≥ 3 states reported by Gu (2005bGu ( , 2007; Kotochigova et al (2007Kotochigova et al ( , 2010 are also of high accuracy. However, Gu (2005bGu ( , 2007 provided energy data for O-like Fe and Ni but not transition rates, and Kotochigova et al (2007Kotochigova et al ( , 2010 only reported transition wavelengths and rates in the range from 12 A to 16Å in Fe XIX.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The data sets of the n ≥ 3 states reported by Gu (2005bGu ( , 2007; Kotochigova et al (2007Kotochigova et al ( , 2010 are also of high accuracy. However, Gu (2005bGu ( , 2007 provided energy data for O-like Fe and Ni but not transition rates, and Kotochigova et al (2007Kotochigova et al ( , 2010 only reported transition wavelengths and rates in the range from 12 A to 16Å in Fe XIX.…”
Section: Introductionmentioning
confidence: 81%
“…Most of them targeted atomic data for low-lying states of the (1s 2 )2s 2 2p 4 , 2s2p 5 , and 2p 6 config-urations (the n = 2 complex) (Baluja & Zeippen 1988a,b;Galavis et al 1997;Vilkas et al 1999;Zhang & Sampson 2002;Gu 2005a;Hu et al 2011;Rynkun et al 2013;Fontes & Zhang 2015). Because of their wide applications for analyzing new observations of astrophysical sources, as well as for modeling and diagnosing a variety of plasmas, energy and transition data for higher-lying states of the n ≥ 3 complexes are also eagerly needed (Phillips et al 1982;Acton et al 1985;Landi & Phillips 2005;Kotochigova et al 2007Kotochigova et al , 2010Raassen & Pollock 2013). Among the studies of the n ≥ 3 states of Fe XIX we mention the calculations of Jonauskas et al (2004) using the multiconfiguration Dirac-Hartree-Fock (MCDHF) method, the calculations of Landi & Gu (2006) using the standard relativistic configuration interaction (RCI) method, the AUTOSTRUCTURE calculations of Butler & Badnell (2008), and the relativistic Breit-Pauli calculations of Nahar (2011).…”
Section: Introductionmentioning
confidence: 99%
“…A general observation is that the quartets states are energetically lower than the doublet states because electron correlation effects are smaller and converge faster with respect to the orbital set for high spin states than for low spin states Galvez et al 2005). The calculations Kotochigova et al (2010).…”
Section: Fe XXmentioning
confidence: 99%
“…, 30 were covered. Kotochigova et al (2010) evaluated the wavelengths and oscillator strengths for the 2s 2 2p 2 3s, 3d → 2s 2 2p 3 , and 2s2p 3 3p → 2s 2 2p 3 transitions in Fe XX using a configuration interaction Dirac-Fock-Sturm (MDFS) method combined with the second-order Brillouin-Wigner perturbation theory. Bhatia et al (1989) determined transition parameters between n = 2 and n = 3 levels of Ar XII, Ti XVI, Fe XX, Zn XXIV, and Kr XXX using the SUPERSTRUCTURE (SS) code.…”
Section: Introductionmentioning
confidence: 99%
“…A significant improvement in accuracy was achieved in the MBPT calculations compared with the results of the RCI method implemented in the FAC code, for example, uncertainties of wavelengths (Gu 2007) were determined to be a few mÅ through extensive comparison with the measurements of Chen et al (2007). The reliability and accuracy of this method were further confirmed by other elaborate theoretical calculations (Kotochigova et al 2007(Kotochigova et al , 2010Ekman et al 2014;Wang et al 2014) and very recent measurements (Gu et al 2011) in the EUV region. The present work has significantly increased the amount of available data for Be-like ions.…”
Section: Comparisonsmentioning
confidence: 70%